2000
DOI: 10.1097/00007632-200005150-00012
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Validity of Radiofrequency Neurotomy for Chronic Lumbar Zygapophysial Joint Pain

Abstract: Lumbar medial branch neurotomy is an effective means of reducing pain in patients carefully selected on the basis of controlled diagnostic blocks. Adequate coagulation of the target nerves can be achieved by carefully placing the electrode in correct position as judged radiologically. Electrical stimulation before lesioning is superfluous in assuring correct placement of the electrode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
398
9
14

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 516 publications
(432 citation statements)
references
References 16 publications
11
398
9
14
Order By: Relevance
“…Other studies supported these data, including one recently published in the Lancet [1,6,8]. On the other hand, other authors showed long-term improvement in pain even for years after the procedure [4,17,19,22].…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Other studies supported these data, including one recently published in the Lancet [1,6,8]. On the other hand, other authors showed long-term improvement in pain even for years after the procedure [4,17,19,22].…”
Section: Introductionmentioning
confidence: 76%
“…The principle is production of heat in order to damage some or all nerve fibers in the target nervous structure (in the case of "conventional" RF) or application of an electromagnetic field to the nervous structure (in the case of pulsed RF), with the ultimate aim of blocking transmission of pain stimuli from peripheral receptors to the central pain structures. In recent years, some publications have reported contradictory results following RF treatment of back pain [1,4,6,8,17,19,22]. On the one hand, Leclaire et al reported that the procedure is effective in terms of pain improvement only in the short term (4 weeks after the procedure) and the improvement failed to last even beyond 12 weeks [8].…”
Section: Introductionmentioning
confidence: 99%
“…A non-randomized study has suggested that there must be at least 80% pain relief from a diagnostic block before permanent denervation is indicated, and selection has to be strict in order to get really good results (Dreyfuss et al 2000). This was not done in one of the trials included in formulating these guidelines (Leclaire et al 2001).…”
Section: Commentsmentioning
confidence: 99%
“…Interventional management of facet arthropathy is done through injection of local anaesthetic (with or without steroid) either within the joint (intra-articular injection) or on to the medial branches [26,31,[35][36][37][38][39][40]. Once diagnosis is confirmed, radiofrequency ablation (RFA) of medial nerves is done for long term effect.…”
Section: Interventional Management Of Facet Painmentioning
confidence: 99%
“…There are also other Interventions that may reduce the incidence of false-positive lumbar facet blocks. These interventions are [26,31,33,35]: -Placebo-controlled blocks, or sequential local anesthetic blocks with two different local anaesthetic of variable duration of action.…”
mentioning
confidence: 99%